2023
DOI: 10.1039/d2en01144a
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to complex metal oxide nanomaterials induces production of reactive oxygen species in bacteria

Abstract: Use of complex metal oxide nanoparticles has drastically risen in recent years, especially due to their utility in electric vehicle batteries. However, use of these materials has outpaced our understanding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…While generally less sensitive than fluorescence techniques, this amperometric method was used successfully to detect micromolar levels of H 2 O 2 formed due to the REDOX transformations of lithium cobalt oxide (LCO) battery materials. 38,39 In our experiments, adding H 2 O 2 to a final concentration of 15 μM in 5 mM EGCG solution increased the current compared to the background current signal when the electrode was immersed in a 5 mM EGCG solution by about 50%. This signal increase indicated that the amperometric detection method was sensitive to the presence of H 2 O 2 in the solution.…”
Section: Reactive Oxygen Species (Ros) Generationmentioning
confidence: 62%
“…While generally less sensitive than fluorescence techniques, this amperometric method was used successfully to detect micromolar levels of H 2 O 2 formed due to the REDOX transformations of lithium cobalt oxide (LCO) battery materials. 38,39 In our experiments, adding H 2 O 2 to a final concentration of 15 μM in 5 mM EGCG solution increased the current compared to the background current signal when the electrode was immersed in a 5 mM EGCG solution by about 50%. This signal increase indicated that the amperometric detection method was sensitive to the presence of H 2 O 2 in the solution.…”
Section: Reactive Oxygen Species (Ros) Generationmentioning
confidence: 62%
“…Examples include flavin adenine dinucleotide (FAD) and related flavins, 53,54 DNA, and RNA. While DNA oxidation has been reported in response to nanoparticle exposure, 23,24 the detailed molecular origins remain unknown. Studies like those reported here may provide key insights into the fundamental chemical origins of nanoparticle interactions with living systems in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies of LiCoO 2 and related molecules under laboratory conditions have frequently observed significant release of Co at concentrations vastly exceeding the aforementioned values. 15,23,24 As a result, it can be concluded that the oxidation-reduction chemistry must also be taking place, with the metal oxide being reduced by one or more solution components. We recently showed that NADH, an important molecule in cellular respiration, interacts strongly with LiCoO 2 via oxidation-reduction (redox) chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…95 Finally, ROS generated during exposures has been identified to increase transformation and mutation Environmental Science: Nano Perspective frequency. 23,96 Thus, the use of ENMs may promote the spread of antibiotic resistance in hospitals and contaminated environmental sites. 97 ENMs are under consideration as emerging pollutants, so action must be taken to provide regulations and guidance for their appropriate disposal and recycling.…”
Section: Outstanding Challenges and Broader Implicationsmentioning
confidence: 99%
“…20 ENM redox properties can cause an oxidative stress response, in addition to exogenous reactive oxygen species (ROS) generation by dissolution of the particles themselves (through Fenton, Fenton-like, Haber Weiss, or light-initiated processes). [21][22][23] ROS contributions to ENM toxicity are difficult to assess due to their apparent non-preferential targeting of biomolecules. In addition, oxidative damage is likely to disturb the function and expression of other systems, making it extremely difficult to map the initial targets of ENM action in comparison to the subsequent effects.…”
Section: Introductionmentioning
confidence: 99%